1983
DOI: 10.1007/bf00228765
|View full text |Cite
|
Sign up to set email alerts
|

Genetic patterns of transcobalamin II and the relationships with congenital defects

Abstract: The vitamin B12-binding protein, transcobalamin II, is a trace component of plasma with a rapid turnover. This protein is essential for absorption, transport, cellular uptake and for recycling of vitamin B12 (cobalamin). Congenital transcobalamin II deficiency, an inborn error of metabolism is inherited as a recessive trait. The homozygous form of the deficiency is accompanied by severe clinical, hematological and immunological disturbances in the first months of life. Analytical, genetic, biochemical and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Cobalamin is taken up by cells only when bound to TCII [8]. The rest of extracellular cobalamin is bound to a group of a-glycoproteins with a high affinity for cobalamin; these are electrophoretically rapid and are called "R-binders" and include transcobalamin I and transcobalamin III [6,8,14]. Their function is not known but it has been suggested that they may act as a transport system to remove noxious cobalamin analogues from the brain and other tissues [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobalamin is taken up by cells only when bound to TCII [8]. The rest of extracellular cobalamin is bound to a group of a-glycoproteins with a high affinity for cobalamin; these are electrophoretically rapid and are called "R-binders" and include transcobalamin I and transcobalamin III [6,8,14]. Their function is not known but it has been suggested that they may act as a transport system to remove noxious cobalamin analogues from the brain and other tissues [15].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the patient is homozygous for an abnormal gene responsible for the lack of B~2 binding capacity and low or undetectable immunoreactive TCII levels. This more common phenotype detected by electrophoresis was first described in a family from Seattle [6]. The patient was commenced on 200 gg of cyanocobalamin i.m.…”
Section: Offprint Requests To: P C J Rogersmentioning
confidence: 95%
See 1 more Smart Citation
“…Serum Cbl levels cannot serve as a diagnostic tool because they show as normal and most of serum Cbl is bound to haptocorrin (or R-binder, formerly named transcobalamin I), a glycoprotein whose function is not fully understood. 4,5 In this study, the genetic work-up of two patients with typical earlyonset TC II deficiency is reported. Exon amplification and sequencing of the TCII gene was uninformative with regard to the definite genetic background in both patients.…”
Section: Introductionmentioning
confidence: 98%
“…Symptoms include megaloblastic anemia and pancytopenia, vomiting, diarrhea and early-onset of failure to thrive, repeated infections, and mental retardation. [4][5][6][7][8] The disorder is inherited in an autosomal-recessive trait and was first described in 1971 in two siblings with megaloblastic anemia and normal levels of serum Cbl. 9 Diagnosis can either be achieved by the measurement of serum transcobalamin by an enzyme-linked immunosorbent assay method 10 or by genetic testing.…”
Section: Introductionmentioning
confidence: 99%